2009
DOI: 10.1139/f09-057
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-fishery or ecosystem conundrum? Multispecies considerations inform thinking on long-term management of North Sea demersal stocks

Abstract: Signatories of the 2002 World Summit on Sustainable Development declaration committed to maintain or restore fish stocks to levels that can produce the maximum sustainable yield (MSY), a goal that has been challenged on a number of grounds. The European Commission has stated an objective to manage fisheries (independently) to achieve MSY by 2015, which has catalysed the Regional Advisory Councils’ (RACs) thinking on MSY and how it relates to their goal of developing long-term management plans. This study uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…but also due to indirect interactions of mixed fisheries (Walters et al, 2005;Mackinson et al, 2009), especially in a fast changing ecosystem such as the Mediterranean. The rapid warming, combined with the expansion of non-indigenous species is definitely changing the suitability of the habitats for traditional commercial species with effects on their resilience to fishing (Libralato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…but also due to indirect interactions of mixed fisheries (Walters et al, 2005;Mackinson et al, 2009), especially in a fast changing ecosystem such as the Mediterranean. The rapid warming, combined with the expansion of non-indigenous species is definitely changing the suitability of the habitats for traditional commercial species with effects on their resilience to fishing (Libralato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The MSY target proves specially challenging in mixed Mediterranean fisheries, where more than a hundred commercial species are landed . As each species has specific MSYs, it is extremely difficult to regulate the fishing mortality for each of them independently (Ratz et al, 2007;Mackinson et al, 2009;Guillen et al, 2013), notably when the dynamics of these species may, in turn, be influenced by the environmental (i.e., climate) and fishing impacts (Mueter and Megrey, 2006). Achieving the MSY goal, therefore, is not an easy task because many different contrasting socioeconomic and ecological interests need to be confronted.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies, however, have suggested that top-down effects, such as predation by sprat on zooplankton, are equally important in what is termed a "wasp-waist" system (14). For demersal piscivorous fish species like cod and whiting, the importance of fishing activity and predator-prey interactions has also been clearly demonstrated (15). Seabirds are also important predators and they are considered sensitive to change in the abundance of planktivorous fish, particularly sandeel and juvenile clupeids, i.e., sprat (14,16,17).…”
mentioning
confidence: 99%